HATCHING PERFORMANCES AND YOLK SAC ABSORPTIONS OF CASPIAN BROWN TROUT (SALMO TRUTTA CASPİUS T., 1954) - M. Kocabaş; N. Başçınar; Ş. A. Şahin; F. Kutluyer (Journal of Animal and Plant Sciences, 2012)
Salmo trutta caspius T., 1954is a native to Caspian Sea and is an important fish species due to its aquaculture potential, economic value and high marketability. The aims of this study were to determine hatching rate, body and yolk weight at hatching, the growth rate during the yolk absorption and yolk conversion efficiency of S. t. caspius larvae. Studies were further extended to determine the relationships between length, total wet weight, dry yolk body weights of alevins and degree-days. Results revealed that the mean wet weight was 16.78 ± 2.17 mg (n = 10) at hatching and reached 52.62 ± 3.55 mg just before the swim-up stage. The mean dry weights of the body and yolk sac were 2.36 ± 0.28 mg and 10.67 ± 0.67 mg at hatching and 7.21 ± 0.71 mg and 2.57 ± 0.62 mg at swim-up stages, respectively. The mean body dry matter and water content of the larvae were 33.10% and 66.90% at hatching and 15.46% and 84.54% of the total biomass at swim-up stages, respectively.  Our results indicated that dry yolk, total larval weights and dry matter of the larvae decreased, while body weight and water content increased with degree-days.  The growth of larva, yolk sac absorption and yolk conversion efficiency were calculated as 0.18 mg/day, 0.23 mg/day and 0.60, respectively. The data collected during these studies contribute to the management practices of  the stocks of this species.
Keywords: Salmo trutta caspius; Hatching rate; Yolk sac absorption; Degree days.